The incidence of raised intracranial pressure in nonsyndromic sagittal craniosynostosis following primary surgery. - Thomas, G; Johnson, D; Byren, J; Judge, A; Jayamohan, J; Magdum, SA; Richards, P; Wall, SA (2015)
OBJECT Raised intracranial pressure (ICP) is recognized to occur in patients with nonsyndromic isolated sagittal craniosynostosis (SC) prior to surgery. However, the incidence of raised ICP following primary surgery is rarely reported and there appears to be a widely held assumption that corrective surgery for SC prevents the later development of intracranial hypertension. This study reports the incidence of postoperative raised ICP in a large cohort of patients with SC treated by 1 of 2 surgical procedures in a single craniofacial unit. METHODS A retrospective review was performed of all patients with SC who underwent either a modified strip craniectomy (MSC) or calvarial remodeling (CR) procedure under the care of the Oxford Craniofacial Unit between 1995 and 2010 and who were followed up for more than 2 years. The influence of patient age at surgery, year of surgery, sex, procedure type, and the presence of raised ICP preoperatively were analyzed. RESULTS Two hundred seventeen children had primary surgery for SC and were followed up for a mean of 86 months. The overall rate of raised ICP following surgery was 6.9%, occurring at a mean of 51 months after the primary surgical procedure. Raised ICP was significantly more common in those patients treated by MSC (13 of 89 patients, 14.6%) than CR (2 of 128 patients, 1.6%). Also, raised ICP was more common in patients under 1 year of age, the majority of whom were treated by MCS. No other factor was found to have a significant effect. CONCLUSIONS Postoperative raised ICP was found in more than 1 in 20 children treated for nonsyndromic SC in this series. It was significantly influenced by the primary surgical procedure and age at primary surgery. Careful long-term follow-up is essential if children who develop raised ICP following surgery are not to be overlooked.